Insights into the Mechanisms Involved in Protective Effects of VEGF-B in Dopaminergic Neurons - Beatrice Caballero; Scott J. Sherman; Torsten Falk (Parkinson's Disease)
Vascular endothelial growth factor-B (VEGF-B), when initially discovered, was thought to be an angiogenic factor, due to its intimate sequence homology and receptor binding similarity to the prototype angiogenic factor, vascular endothelial growth factor-A (VEGF-A). Studies demonstrated that VEGF-B, unlike VEGF-A, did not play a significant role in angiogenesis or vascular permeability and has become an active area of interest because of its role as a survival factor in pathological processes in a multitude of systems, including the brain. By characterization of important downstream targets of VEGF-B that regulate different cellular processes in the nervous system and cardiovascular system, it may be possible to develop more effective clinical interventions in diseases such as Parkinson’s disease (PD), Amyotrophic Lateral Sclerosis (ALS), and ischemic heart disease, which all share mitochondrial dysfunction as part of the disease. Here we summarize what is currently known about the mechanism of action of VEGF-B in pathological processes. We explore its potential as a homeostatic protective factor that improves mitochondrial function in the setting of cardiovascular and neurological disease, with a specific focus on dopaminergic neurons in Parkinson’s disease.